A novel device for detection of soft tissue inflammation: dynamic behaviour of a functionally graded AFM cantilever. (1st January 2012) - Firoozbakhsh, Keikhosrow; Ahmadian, Mohammad Taghi; Rahaeifard, Masoud; Kahrobaiyan, Mohammad Hossain
Atomic force microscopes (AFM) are devices used for surface roughness detection. A novel AFM device composed of a tip attached to a cantilever beam is proposed for precise soft-tissue-inflammation detection. It is assumed that the beam is made of functionally graded materials (FGMs) with properties varying throughout the thickness. Two low resonant frequencies and the sensitivities of the AFM cantilever are studied. A relationship is developed to evaluate the sensitivity of a FGM micro-cantilever beam. The effects of mass distributions of material constituents, surface contact stiffness, and geometric parameters on the resonant frequencies and sensitivities are studied. The high sensitivity of such device to the stiffness of the contact surface is proposed to be the recognition key for soft tissue inflammation.